1977
DOI: 10.1161/01.res.40.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins and the control of blood flow in the canine myocardium.

Abstract: SUMMARY A comprehensive study was undertaken to evaluate the effects of inhibition of prostaglandin (PG) synthesis on a variety of reactions in the coronary vascular bed of anesthetized, open-chest dogs. In 23 dogs an electromagnetic flow probe (EMFP) and hydraulic occluder were placed around either the left anterior descending or circumflex branches of the coronary artery and a needle was inserted distal to the EMFP. Injections into the coronary artery of arachidonic acid (AA), bradykinin, adenosine, angioten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(31 citation statements)
references
References 34 publications
4
26
1
Order By: Relevance
“…Furthermore, an infusion of indomethacin produced blockade of the coronary actions as well as the PGL efflux (Schror, Moncada, Ubatuba & Vane, 1978). These data corroborate previous experiments in which NSAA was administered to inhibit prostaglandin synthetase in isolated perfused or intact hearts (Minkes, Douglas & Needleman, 1973;Needleman, 1976;Hintze & Kaley, 1977). Other polyunsaturated fatty acids have also been reported to produce changes in coronary flow and in the output of PGL (Mentz & Forster, 1977).…”
Section: Introductionsupporting
confidence: 87%
“…Furthermore, an infusion of indomethacin produced blockade of the coronary actions as well as the PGL efflux (Schror, Moncada, Ubatuba & Vane, 1978). These data corroborate previous experiments in which NSAA was administered to inhibit prostaglandin synthetase in isolated perfused or intact hearts (Minkes, Douglas & Needleman, 1973;Needleman, 1976;Hintze & Kaley, 1977). Other polyunsaturated fatty acids have also been reported to produce changes in coronary flow and in the output of PGL (Mentz & Forster, 1977).…”
Section: Introductionsupporting
confidence: 87%
“…Also, previous studies have shown that indomethacin does not affect coronary vascular responsiveness. 19 Our preliminary study in seven other normal rabbit hearts without any inotropic intervention showed that left ventricular peak isovolumic pressure at a constant ventricular volume at 90 and 120 minutes after an initial measurement (+0.4+10.0% and -6.2±15.4%, respectively) did not significantly differ from the initial value of 98+13 mm Hg. This indicates stability of our cross-circulated heart preparation compared with crystalloid-perfused hearts.…”
Section: Materials and Methods Animal Modelsmentioning
confidence: 75%
“…PGE 2 reportedly promotes the second phase of platelet aggregation. 23 ' 24 While it is doubtful that unregulated PGE 2 formation by spontaneous hydrolysis of PGH 2 contributes to carotid arterial thromboregulatory mechanisms, PGE 2 formed nonenzymatically could oppose platelet inhibitory effects of PGI 2 . Previous work in our laboratory, which unmasked the presence of GSH-dependent PGE 2 isomerase activity in bovine coronary artery microsomes, demonstrated the need for appropriately controlled experiments before the presence of GSH-dependent PGE 2 isomerase in vascular tissues could be definitely excluded.…”
Section: Discussionmentioning
confidence: 99%